How resilient are farming households and communities to a changing climate in Africa? A gender-based perspective. (September 2015) - Perez, C.; Jones, E.M.; Kristjanson, P.; Cramer, L.; Thornton, P.K.; Förch, W.; Barahona, C.
Highlights: Rights, social relations, organizations and policies shape vulnerability. Policies take away communities tm) traditional natural resources decision-making. Agriculture and livestock production agencies show great anti-women biases. Women are more vulnerable than men but may have similar or better adaptive capacity. Abstract: In this paper we examine conditions that underlie vulnerability and resilience possibilities for households and communities that face and respond to climate- and other changes, in nine East and West African countries. We base our analysis on a unique integrated qualitative and quantitative dataset composed of household surveys and village focus group studies carried out across a wide range of environments and agricultural systems. We identify human population growth, commercialization of the economy, and natural resource use policies, in addition to weather, as key drivers of change. We compare the agricultural and livelihood systems of male and female respondents, as well as their productive resources, organization and access to services. Women have less access than men to common property resources, as well as to cash to obtain goods or services. Women control less land than men, the land they control is often of poorer quality, and their tenure is insecure. Women engage in mutual insurance and risk-sharing networks, and benefit from non-agricultural services provided by social support institutions external to the village. Formally registered, public and private external organizations that foster agriculture and livestock production have tremendous anti-women biases, and tend to provide support primarily to men. Policies and strategies are needed to eliminate those prejudices so that men and women increase their resilience and manage well their changing environments.